Urinary Tract Infection Bacterial at RSUP H. Adam Malik Medan in 2019: an Overview Study - Teguh Firdaus; Rina Yunita (Talenta Publisher, 2021)
Urinary Tract Infection (UTI) is the second-largest infection after respiratory tract infection (WHO, 2013). The prevalence of UTI in Indonesia is relatively high. UTI originated from the invasion and proliferation of microorganisms into the urinary tract in meaningful quantities. Gram-negative bacteria are mostly the cause of UTI including E. coli, Klebsiella sp, Enterobacter sp, and Proteus sp. Patients with UTI with inadequate treatment can experience complications e.g., acute renal failure and urosepsis. This study aims to find out the profile of bacteria that cause UTI at RSUP H. Adam Malik Medan in 2019. This descriptive study is using a non-analytical retrospective approach conducted to secondary data from urinary culture examination at RSUP H. Adam Malik Medan. Data were analyzed using the SPSS 24. Gram-negative bacteria results of 72.7% with E. coli postulated as the most common etiology (33,3%) and gram-positive bacteria results of 27.3%, dominated by Enterococcus faecalis (16.3%). The sensitivity study exhibited various results e.g., 100%, 98.2%, and 97.0% in E. coli for Tigecycline, Meropenem, and Amikacin respectively. Enterococcus faecalis also posed a similar results regarding its sensitivity result to different antibiotics. Gram-negative bacteria are the most common bacterial etiology of UTI, specifically E. coli with comparable sensitivity results